Toward evidence-based laser dentistry: wavelength selection, parameter standardization and clinical outcomes - Almiqdad Dashti; Mohammad Reda; Abdulaziz Abdullah; Abdulaziz AlAdwani; Ahmad Alibrahim; Ali Shukrallah; Husain Alshakhs; Ahmad Alsediqi; Anfal Alsanea; Fahad Bohendi Alali; Wadhah Alotaibi; Reem Alkandari; et al. (International Journal Of Community Medicine And Public Health, 2026)
Lasers in dentistry represent a range of wavelength-specific technologies and biological mechanisms rather than a uniform treatment category. This structured comprehensive narrative review examined the principal foundations and clinical domains of contemporary laser dentistry, including laser–tissue interaction, wavelength and parameter selection, periodontics and peri-implant therapy, endodontics, restorative dentistry, prosthodontics, oral surgery, pediatric dentistry, orthodontics, photobiomodulation, and antimicrobial photodynamic therapy. Literature from PubMed, Scopus, and Web of Science was reviewed and interpreted comparatively according to wavelength, target chromophore, emission characteristics, operating parameters, clinical indication, comparator, outcome measures, and degree of clinical support. The evidence showed considerable variation across applications. Selected soft-tissue surgical procedures and wavelength-matched ablative or debonding applications had the clearest clinically established roles, although superiority over conventional approaches was not universal. In periodontics, peri-implant therapy, and endodontics, lasers and antimicrobial photodynamic therapy were better supported as adjuncts to mechanical debridement or chemomechanical disinfection than as independent alternatives. Prosthodontic applications offered useful options for material-specific surface treatment and conservative restoration retrieval, although their effectiveness remained dependent on substrate characteristics and thermal control. Pediatric applications appeared relevant to minimally invasive care and patient acceptance. In orthodontics, evidence was stronger for selected soft-tissue procedures and ceramic bracket debonding than for accelerating tooth movement or consistently reducing pain. The available evidence indicates that lasers should not be considered a single therapeutic category or a universal replacement for conventional methods. Their clinical value is indication-specific and, in many applications, primarily adjunctive.